Editorial: Interdisciplinary research in services marketing - Christofi, Michael; Kvasova, Olga; Hadjielias, Elias (My University, 2023)
Purpose: This paper aims to highlight the importance of interdisciplinary services marketing research and identify basic prerequisites for inter-disciplinary work in the field of services marketing, and to offer directions to services marketing scholars regarding future interdisciplinary research work. Design/methodology/approach: Building on the available literature, the authors argue for the importance of interdisciplinary research in services marketing. The authors also develop a framework featuring “the key challenges impeding interdisciplinarity”, which need to be addressed to shift the services marketing field towards more sensible interdisciplinarity. Further, based on literature synthesis from different disciplines, they provide a framework with “four future research avenues for interdisciplinary research in services marketing”. Findings: The authors identify five challenges that can likely impede services marketing research from progressing into true interdisciplinary work: limited cross-pollination, limited paradoxical thinking, limited conceptual development, limited cross-disciplinary collaboration and “inside–out” focus. The authors also propose four future research avenues to drive interdisciplinary research in the services marketing field: integration of services marketing and information management; linguistic perspectives in services marketing research; the interface between services marketing and medicine; and consumer personality and values in services marketing. Originality/value: The authors propose two novel frameworks. The first concerns the key challenges of interdisciplinarity in services marketing research and the second provides avenues to drive future interdisciplinary services marketing research.
Keywords: Conceptual; Digital; Interdisciplinarity; Interdisciplinary research; Marketing; Service strategy; Services; Services marketing